2022
DOI: 10.1080/14756366.2022.2096018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of glucosamine-6-phosphate synthase as potential antimicrobials or antidiabetics – synthesis and properties

Abstract: Glucosamine-6-phosphate synthase (GlcN-6-P synthase) is known as a promising target for antimicrobial agents and antidiabetics. Several compounds of natural or synthetic origin have been identified as inhibitors of this enzyme. This set comprises highly selective l -glutamine, amino sugar phosphate or transition state intermediate cis -enolamine analogues. Relatively low antimicrobial activity of these inhibitors, poorly penetrating microbial cell membranes, has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…Interestingly, while glucosamine-6-phosphate synthase was identified as an essential reaction in both single-species models, the lethal phenotype conferred by deleting this reaction would be recovered by a simple exchange of acetylglucosamine between the bacteria. Therefore, efforts using therapeutic agents which inhibit this enzyme 52 would need to consider the potential role of acetylglucosamine found in the environment or leaked by resistant bacteria in the consortia.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, while glucosamine-6-phosphate synthase was identified as an essential reaction in both single-species models, the lethal phenotype conferred by deleting this reaction would be recovered by a simple exchange of acetylglucosamine between the bacteria. Therefore, efforts using therapeutic agents which inhibit this enzyme 52 would need to consider the potential role of acetylglucosamine found in the environment or leaked by resistant bacteria in the consortia.…”
Section: Resultsmentioning
confidence: 99%
“…UDP-GlcNAc is the donor sugar for O-GlcNAcylation, and studies had shown that increased O-GlcNAcylation could promote the progression of hepatocellular carcinoma [ 39 ]. In addition, the synthesis enzyme of Glucosamine 6-phosphate, Glucosamine-6-phosphate synthetase, is also considered a potential carcinofetal marker [ 40 ] and a promising target for antimicrobial and antidiabetic drugs [ 41 ]. Therefore, the alterations in AML glucose metabolism primarily manifest as enhanced glycolysis, antioxidant activity, and glycosylation modifications.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the binding affinity of these new 3-furan-1-thiophene-based chalcones against the respective proteins, in silico studies were performed on GlcN-6-P synthase (glucosamine-6-phosphate synthase), the target enzyme for antimicrobial drugs [ 34 ] and colchicine binding site in tubulin, are the target receptors for anticancer drugs [ 35 ]. GlcN-6-P synthase binding site involves eight amino acids, these are Thr302, Ser303, Ser347, Gln348, Ser349, Thr352, Val399, and Ala602, while the binding pocket of tubulin comprises Val181, Leu248, Ala250, Leu255, Met259, Ala316, and Lys352.…”
Section: Introductionmentioning
confidence: 99%